2020
DOI: 10.1039/d0na00521e
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetics and clearance of inhaled gold ultrasmall-in-nano architectures

Abstract: Among the organism’s entry portals, the respiratory tract is one of the most promising routes for a non-invasive administration of therapeutics for local and systemic delivery. On the other hand,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…The presence of USNPs within NAs was shown previously [ 47 ]. Here, the differences in the TEM and DLS measurement confirm the successful decoration of NAs with HSA without affecting the structure of the final nano-architectures.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The presence of USNPs within NAs was shown previously [ 47 ]. Here, the differences in the TEM and DLS measurement confirm the successful decoration of NAs with HSA without affecting the structure of the final nano-architectures.…”
Section: Resultssupporting
confidence: 58%
“…We observed a very promising biosafety profile in zebrafish models [ 55 ], and confirmed these data further in healthy murine models [ 38 ]. Furthermore, we investigated the biokinetics of standard Nas in animal models and confirmed that the building blocks are metabolized or excreted after biodegradation [ 47 ]. Finally, it is important to highlight that the hydrodynamic diameter of Nas is not significantly altered over 8 h incubation in blood-mimicking solutions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight here that there is only one site where the nervous system of mammals is directly exposed to the external environment. This is the roof of the nasal cavity which represents the intranasal route and has been investigated for nanoparticle entry into the brain bypassing the BBB [ 49 ]. Direct uptake of nanoparticles into the nervous system might occur in this site thus it can be another viable administration route that deserves to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasmall gold nanoparticles could be completely eliminated from other secondary organs within 10 d. This study lays the foundation for the use of metal in the treatment of lung tumors, asthma, and other respiratory diseases. [ 146 ]…”
Section: Factors Affecting Renal Clearancementioning
confidence: 99%